Type-2 fuzzy logic controller optimized by wavelet networks for mobile robot navigation - Fatma Affane; Kadda Zemalache Meguenni; Abdelhafid Omari (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this work, we will use a new control strategy based on the integration of a type-2 fuzzy reasoning optimized by wavelet networks as part of a navigation system of a mobile robot. The proposed approach is able to facilitate the navigation task in an autonomous manner, in order to determine which commands must be sent at each moment to the mobile robot. This operation must take into account convergence towards a goal with the shortest possible path in the minimum delay between the starting position and the target position. Once the goal is reached, the robot stops.